Helicobacter pylori causes gastrointestinal hemorrhage in patients with congenital bleeding disorders - Schulman, Sam; Rehnberg, Ann-Sofie; Hein, Marju; Hegedus, Olga; Lindmarker, Per; Hellström, Per M. (Thrombosis and Haemostasis, 2003)
Helicobacter pylori (H. pylori) infection is associated with peptic ulcer disease and gastric cancer. The eradication of H. pylori is of special interest in patients with congenital bleeding disorders, for whom treatment of gastrointestinal hemorrhage with factor concentrates is costly. The prevalence of H. pylori varies between different populations and identification of high-risk subgroups may allow for more targeted screening and eradication of the infection. We performed a 5-year retrospective study of gastrointestinal bleeding, combined with screening and treatment for H. pylori and a long-term prospective follow-up in 168 Swedish and 23 Estonian patients with hemophilia or von Willebrand disease. The prevalence of seropositivity was lower in Sweden than in Estonia (28 versus 48%, p = 0.03), lower in native Swedes than in non-Nordic immigrants to Sweden (20 versus 76%, p = 0.0001) and lower in patients less than 40 years of age than older patients (16 versus 38%, p = 0.002). The incidence of gastrointestinal hemorrhages among the 35 Swedish patients with active H. pylori infection, confirmed by a urea breath test, was 6.0 per 100 patient-years before eradication therapy versus 1.7 during the prospective followup. A negative urea breath test one month after therapy always remained negative after one year. Screening, followed by treatment of all infected patients, yielded a reduction of direct costs over a 5-year period of 130 US-$ per screened patient. We conclude that screening and eradication therapy for infection with H. pylori in patients with congenital bleeding disorders is an effective and economic strategy.
Keywords: Hemophilia; von Willebrand Disease; gastrointestinal hemorrhage; Helicobacter pylori; urea breath test; health economy